(untitled) (Applied Biological Research, 2025)
Aonla (Phyllanthus emblica) is widely used in the Ayurvedic and pharmaceutical industries due to the presence of medicinally important bioactive compounds. In the present study, seven commercial cultivars of P. emblica along with one wild genotype were characterized for morpho-molecular traits and antioxidant potential. Morphological evaluation was conducted using a randomized block design, while molecular analysis was carried out using random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) markers. Pomological traits exhibited significant variation among the evaluated cultivars. Principal component analysis explained 75.1% of the total variation in fruit traits, clustering all commercial cultivars together and separating the wild genotype into a distinct group. The commercial cultivars were superior in all fruit traits and showed higher antioxidant potential compared to the wild genotype. Molecular characterization revealed a mean polymorphic information content (PIC) value of 0.51 with 76.7% polymorphism. At the cultivar level, polymorphic loci ranged from 79.2% in cv. Kanchan to 95.2% in cv. Krishna. Shannon’s information index varied from 0.28 in the wild genotype to 0.37 in cv. NA-7, indicating considerable genetic diversity. Cluster analysis using the UPGMA method showed a minimum similarity coefficient of 0.53 between the wild genotype and cv. Kanchan. The combined pomological and molecular results confirmed substantial variability among the evaluated aonla cultivars and demonstrated the usefulness of these approaches for precise characterization of P. emblica genotypes, which can be effectively exploited in future varietal improvement programmes.